ESTIMASI NILAI PEMULIAAN BOBOT SAPIH SAPI PERANAKAN ONGOLE (PO) DI DESA WAWASAN KECAMATAN TANJUNGSARI KABUPATEN LAMPUNG SELATAN - Linda Safitri, M. Dima Iqbal Hamdani, Ali Husni, dan Sulastri (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2019)
This study aims to determine the heritability value and breeding value of weaning weight of Ongole crossbreed (PO) cattle in Wawasan Village, Tanjungsari District, South Lampung Regency. The study was conducted in Wawasan Village Tanjungsari District South Lampung Regency on May 2018 to August 2018. The research material consisted of a recording of the birth of the cows, the birth weight of the parents, the weaning weight of the parents, the age of weaning parents, the age of the parents at the time of birth, the weight of the female calves, weaning weight of female calves and weaning age of the parents which gave birth twice in 2015 to 2017. This study uses survey method. Data analysis was done by looking for corrected weaning weights, estimated heritability values, and breeding values of weaning weights in PO cattle in Wawasan Village, Tanjungsari District, South Lampung Regency. Based on the results of the study showed PO cattle in Wawasan Village, Tanjungsari District, South Lampung Regency the average corrected weaning weight of the parents were 98.87±1.79 and the average calf corrected weights were 140.64±38.87; heritability value of weaning weight were 0.40; and the average breeding value were 140.64±15.24. Calculation of breeding values shows that there are 54% of PO cattle that have above-average breeding values. Keywords: Breeding value, Heritability, Ongole crossbreed, Weaning weight